Penyuluhan Kata Baku dan Tidak Baku pada Siswa SMPIT Sabilulhuda Kota Cirebon - Mia Fatimatul Munsi; Ismawar Ismawar; Dessy Kushardiyanti (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2024)
This service aims to provide counseling about the importance of using standard Indonesian as a form of positive attitude towards Indonesian. In its implementation, counseling was carried out to 15 class VIII A students of SMPIT Sabilulhuda Cirebon City. The method used is counseling method. This activity is motivated by mistakes and language errors that are still found in the community, especially among students. In addition, this service is also carried out based on the results of integrating learning from the Language Error Analysis course with Community Service activities. As for the results of counseling activities using standard and non-standard words, 26.66% of students were in the good category, 53.33% were in the enough category, and 20% were in the bad category. So, it can be concluded that 80% of students understand what has been conveyed in counseling. Extension activities of this kind must continue to be carried out in order to minimize errors and mistakes in the Indonesian language. In addition, inviting students to practice the knowledge gained in learning subjects to make it more meaningful and useful for society.Â